Návrh správkové hmoty se sníženou elektrickou impedancí - Žáková, Karolina (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Tato bakalářská práce se zaměřuje na návrh nového složení správkové hmoty na silikátové bázi s cílem snížit elektrickou impedanci. V teoretické části budou popsány základní pojmy potřebné k pochopení tématu práce, jako jsou pojmy související s vodivostí, silikáty, kompozity a obecně správkovými hmotami. Experimentální část zahrnuje výběr surovin, přípravu a testování různých složení správkových hmot s odlišnými plnivy. Bude zkoumán vliv různých přísad na elektrické vlastnosti správkové hmoty, včetně dopadu na její vodivost, rezistivitu a soudržnost. Poslední část zahrnuje shrnutí a zhodnocuje dosažené výsledky.

This bachelor's thesis focuses on designing a new composition of corrective material based on silicate with the aim of reducing electrical impedance. In the theoretical part, fundamental concepts necessary for understanding the topic will be described, such as terms related to conductivity, silicates, composites, and corrective materials in general. The experimental section includes the selection of raw materials, preparation, and testing of various compositions of corrective materials with different fillers. The impact of various additives on the electrical properties of the corrective material will be investigated, including its conductivity, resistivity, and cohesion. The final section summarizes and evaluates the achieved results.
Design of repair material with reduced electrical impedance
Keywords: Správková hmota; cement; polymer; kompozit; chytrý beton; druhotné suroviny; grafit; silikáty; soudržnost; elektrická impedance; vodivost; rezistivita; Repair material; cement; polymer; composite; smart concrete; secondary raw materials; graphite; silicates; cohesiveness; electrical impedance; conductivity; resistivity.